2018
DOI: 10.3310/hsdr06260
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hospital emergency readmission and mortality rates in patients with heart failure or chronic obstructive pulmonary disease: a national observational study

Abstract: BackgroundHeart failure (HF) and chronic obstructive pulmonary disease (COPD) lead to unplanned hospital activity, but our understanding of what drives this is incomplete.ObjectivesTo model patient, primary care and hospital factors associated with readmission and mortality for patients with HF and COPD, to assess the statistical performance of post-discharge emergency department (ED) attendance compared with readmission metrics and to compare all the results for the two conditions.DesignObservational study.Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 67 publications
3
18
1
1
Order By: Relevance
“…Previous COPD and non-COPD hospitalisations in the previous year also significantly increased the risk for 30-day readmission by 53% to 56% and 60% to 64%, respectively [38,39]. Consistent with other studies, GOTO et al [31] found that frequent exacerbators (defined as two hospitalisations in the past year) BOTTLE [21] GERSHON [32] GOTO [31] JACOBS [35] SHARIF [44] SIMMERING [45] TZY-CHYI YU [48] Overall (I 2 =95.4%, p=0.000) had a 2.5-fold increase in odds of readmission compared to non-frequent exacerbators. Disease severity of COPD was also a risk factor for readmission and has been evaluated using different tools.…”
Section: Meta-analysis Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Previous COPD and non-COPD hospitalisations in the previous year also significantly increased the risk for 30-day readmission by 53% to 56% and 60% to 64%, respectively [38,39]. Consistent with other studies, GOTO et al [31] found that frequent exacerbators (defined as two hospitalisations in the past year) BOTTLE [21] GERSHON [32] GOTO [31] JACOBS [35] SHARIF [44] SIMMERING [45] TZY-CHYI YU [48] Overall (I 2 =95.4%, p=0.000) had a 2.5-fold increase in odds of readmission compared to non-frequent exacerbators. Disease severity of COPD was also a risk factor for readmission and has been evaluated using different tools.…”
Section: Meta-analysis Resultssupporting
confidence: 59%
“…Patients' insurance was reported as a risk/protective factor in five studies: four in the USA and one in Europe [19,31,35,38,40] (tables S2 and S3). Smaller hospital size (<100 beds) and fewer doctors were reported as significant readmission risk factors with 2.27-fold and 67% increased odds of readmission, respectively [21]. Staying in medium-sized hospitals compared to large hospitals decreased the odds of readmission by 5% [35].…”
Section: Behavioural Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study emphasized the clinical index, including age, prior missed outpatient appointments, length of hospital stay, and comorbidities, to predict readmission [15]. However, the most valuable index is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sarcopenia was associated with 1-year mortality in individuals < 75 years old but not in older patients. It is likely that other factors (e.g., cognitive and socioeconomic factors, adherence to follow-up, type of comorbidities, and number of comorbidities) exert a more consequential effect than sarcopenia on the survival of the elderly [20, 21]. …”
Section: Discussion/conclusionmentioning
confidence: 99%